2021
DOI: 10.1136/bmjopen-2020-047244
|View full text |Cite
|
Sign up to set email alerts
|

Association between community deprivation and practising health behaviours among South Korean adults: a survey-based cross-sectional study

Abstract: ObjectivesThis study aimed to determine the association between community deprivation and poor health behaviours among South Korean adults.DesignThis was a survey-based cross-sectional study.Setting and participantsData of 224 552 participants from 244 communities were collected from the Korea Community Health Survey, conducted in 2015.Primary and secondary outcome measuresWe defined health behaviours by combining three variables: not smoking, not high-risk drinking and walking frequently. Community deprivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The KCHS received Korea Centers for Disease Control and Prevention (KCDC) IRB approval (2016-10-01-P-A) in 2016. From 2017, the ethics approval for the KCHS was waived by the KCDC IRB as it does not fall under human subject research based on the enforcement rule of the bioethics and safety act [ 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The KCHS received Korea Centers for Disease Control and Prevention (KCDC) IRB approval (2016-10-01-P-A) in 2016. From 2017, the ethics approval for the KCHS was waived by the KCDC IRB as it does not fall under human subject research based on the enforcement rule of the bioethics and safety act [ 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Invariably, almost any research study on hearing loss published today will provide a background for the research by saying something like "hearing loss is important because hearing loss is risk for dementia" (including papers that we have co-authored, e.g. (Allum, Meredith, Uus, Kirkham, & Dawes, 2023;Dawes et al, 2015;Taylor, Dawes, Kapadia, Shryane, & norman, 2023)). Implicit in these statements is the idea that addressing dementia is more important than addressing hearing loss.…”
Section: Where To From Here?mentioning
confidence: 99%
“…In actual fact, hearing loss is one of the largest sources of burden in terms of years lived with disability ( Mathers & Loncar 2006 ) and a major public health challenge. Invariably, almost any research study on hearing loss published today will provide a background for the research by saying something like “hearing loss is a marker of risk for dementia” (including papers that we have coauthored, e.g., Allum, Meredith, Uus, Kirkham & Dawes 2023 ; Dawes et al 2015 ; Taylor, Dawes, Kapadia, Shryane & Norman 2023 ). Implicit in these statements is the idea that addressing dementia is more important than addressing hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Research reported around the world confirms that area-based deprivation indexes are associated with equity in health status and health outcomes measured in terms of morbidity and mortality. Area-based deprivation was found to be associated with higher cancer mortality in Hong Kong, China [25] and with higher levels of anxiety among patients with advanced cancer in the United States [26], while a South Korean study suggested community deprivation levels to influence individual health behaviors [27]. A Northern Ireland study reported a significant correlation of the prescribing of multiple drug classes with socio-economic deprivation levels [28].…”
Section: Discussionmentioning
confidence: 99%